Employer Branding Through Digital Human Resourches Management - Herawati, Niken; Warpindyastuti, Lady Diana; Aris Hidayat; Addin, Syahrial; Azizah, Ayu; Ulum, Khoirul (Innovative: Journal Of Social Science Research, 2025)
Information and communication technology development has driven significant transformation in various aspects of human resource management, now known as Digital Human Resource Management (Digital HRM). Digital HRM refers to using digital technology to support and enhance key HR functions such as recruitment, training, performance management and employee relations. This transformation not only improves operational efficiency, but also enables a more strategic and data-driven approach to HR decision-making. This article discusses the basic concepts of Digital HRM, the benefits and challenges of its implementation, and its impact on the role of HR in the digital era. The findings show that HR digitalization provides opportunities for innovation in HR management, but also requires organizational readiness in terms of infrastructure, digital competencies, and changes in work culture. Thus, Digital HRM is a key element in creating an adaptive and highly competitive organization amidst the dynamics of the modern business environment.